Diseño de inversor trifasico para sistemas fotovoltaicos residenciales con capacidad menor a 3kW (2021)
Today, the generation of alternative energy has had a strong impact on different sectors of the economy, and brings with it relevant lines in electrical engineering in ways to capture the greatest energy, storage and distribution. These are straightforward with the development of devices based on power electronics, capable of taking the energy generated from these fuels and transforming them according to a specific requirement. Such devices as charge controllers, capacities to capture the most powerful points on the generation fuels, the inverters with the purpose of transforming this energy into regular consumption fuels according to the market specifications. For this reason, different use cases applied to these technologies have been considered, such as: reactive static compensators, harmonic compensation, power factor correction, etc., trying to reduce the magnitude of these problems. In this way, the next project is introduced, showing the process of modular devices capable of addressing a problem related to energy conversion for on-line load equipment present in the residential sector through energy optimization systems. treatment, switching and filtration of three-phase signals.--Taken from the Degree Document Format.